Acute retrograde tibiotalocalcaneal nailing in osteoporotic periarticular ankle fractures - Herrera-Perez, Mario; Martín-Vélez, Pablo; Rendón-Díaz, Diego; Pais-Brito, José Luis (Journal of the Foot & Ankle, 2020)
Objective: This study aimed to report the short-term results of retrograde tibiotalocalcaneal (TTC) nailing in a selected series of patients with fragility ankle fractures. Methods: This study included 17 patients who underwent primary retrograde TTC nailing from January 2016 to April 2019. The Olerud-Molander ankle score (OMAS) was recorded preoperatively and at the final follow-up. Results: Mean patient age was 81.5 years (range, 67-91 years), and mean follow-up duration was 20.9 months (range, 8-50 months). No patient was lost to follow-up. Eleven patients had diabetes. Thirteen patients were able to walk with an assistive device, and 4 with help from another person. Two patients died at 8 and 9 months after treatment. Radiographic healing was observed in 100% of the fractures. No deep infection or scarring problems were recorded. Two patients were wheelchair bound after treatment, whereas 15 recovered their previous autonomy. The mean OMAS score changed from 64.1 (range, 55-75) preoperatively to 55.3 (range, 45-65) postoperatively. Conclusion: Our results suggest that primary retrograde TTC nailing is a valid option in selected patients with fragility ankle fractures, multiple comorbidities, poor soft tissue condition, and difficulty in walking before the fracture. Level of Evidence IV; Therapeutic Studies, Case Series.